Sexual violence in older adults : a Belgian prevalence study - Adam, Stéphane (medRxiv, 2021)
Background: Sexual violence (SV) is an important public health problem which may cause long-lasting health problems. SV in older adults remains neglected in research, policies and practices. Valid SV prevalence estimates and associated risk factors in older adults are currently unavailable. Objective: To measure lifetime and past 12-months sexual victimisation in older adults living in Belgium, its correlates, assailant characteristics and the way that victims framed their SV experiences. Design: Cross-sectional general population study. Setting: Community-dwelling, assisted living and nursing homes. Participants: 513 people of 70 years and older living in Belgium. Methods: SV was measured using behaviourally specific questions based on a broad definition of SV. Participants were selected via a cluster random probability sampling with a random route finding approach. Information on sexual victimisation, correlates, assailant characteristics and framing was collected via structured face-to-face interviews. Results: Lifetime SV prevalence was 44% (55% F, 29% M). Past 12-months prevalence was 8% (9% F, 8% M). Female sex and a higher number of sexual partners were associated with lifetime SV (p <.05), non-heterosexual sexual orientation with past 12-months SV (p <.05). Correlates generally linked to elder abuse and neglect were not linked with SV. ‘Someone unknown’ was identified as most common assailant. Conclusions: SV appears to be common in older adults in Belgium. Both correlates and assailant characteristics seem to differ from previous studies on elder abuse and neglect. Recognising older adults as a risk group for sexual victimisation in research, policies and practices is of the utmost importance